Directed deprotonation-transmetallation of 4-bromopyridine: Flexible routes to substituted pyridines - Gunter Karig (2018)
Halide-directed deprotonation and Li-Zn exchange of 4-bromopyridine 4 provides organozinc 6, which undergoes Pd-mediated coupling to give the 3-aryl-4-bromopyridines 7. Further substitution is achieved to provide the 3,4-disubstituted pyridines 8 and 9, and the 3,4,5-trisubstituted variants 10.